Gastronomy and Urban Space. Changes and Challenges in Geographical Perspective. - (:unkn) unknown (Springer, 2020)
This book focuses on the relationship between gastronomy and urban space. It highlights the intrinsic role of eating establishments and the gastronomy industry for cities by assessing their huge impacts on urban changes and discussing some of the challenges posed by new developments. Written by authors with a background in geography, it starts by discussing theoretical aspects of studies on gastronomy in urban space to place the subject in the broader context of urban geography. Covering both changes and challenges in gastronomy in urban space, it presents a wide range of problems, which are described and analysed using various case studies from Europe and other parts of the world.
Keywords: Gastronomie; Betriebsstandort; Stadtraum; Innenstadtbereich; Stadtrand; Restaurant; Cafe; Nachtleben; Verbraucherverhalten; Freizeitverhalten; Stadtgeographie; Fremdenverkehr; Street Food; Bringdienst